Client risk calibration in PCAOB audits: an analytical procedures panel risk assignment protocol. (2016) - Lusk, Edward J.; Halperin, Michael
Analytical procedures are recommended by the AICPA to calibrate the risk level of the audit. In this paper, we detail an Analytical Procedures technique to aid in assigning an initial risk level to the audit client. Following the AICPA analytical procedures guide, we offer a panel analytical procedures model that uses a priori accrued firms to form benchmarking triage for the main effect: risk level. After testing for the expected fixed effects of the firm benchmarks and also for the explicit input variable power, we show that the panel risk assignment protocol (PRAP) only needs a set of high risk firms as the client benchmarking group. We offer six other sources of risk-related information that may inform the audit regarding client relative risk at the planning stage of the audit. Finally, the final scoring of the risk level is produced by a VBA-Excel decision support system that is available free as a download without restrictions on its use.